Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1203/00006450-198111000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperinsulinemia Reduces Surface Active Material Flux in Tracheal Fluid of Fetal Lambs

Abstract: SummaryWe sought to test the hypothesis that hyperinsulinemia per se alters the flux of surface active material (SAM) into tracheal fluid by continuously infusing insulin (0.24 + 0.04 units/kg/hr, mean + S.E.) from 112 through 135 days gestation into five chronically catheterised fetal lambs, from which tracheal fluid could be collected.Serum insulin levels in these fetuses (95 f 10 pU/ml) were greater than in five chronically catheterised control fetuses of the same gestational age (10 f 1 pU/ml, P < 0.001) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The control fetuses reported here underwent significant lung maturation in response to cortisol, as reflected by large and statistically significant increases in SAM flux into their tracheal fluid and in their tracheal fluid phospholipid content, which were much greater than those that occur between days 128 and 130 of gestation during normal maturation of fetal lamb lungs (10,11,23 The dose of cortisol infused to both glucose-treated and control fetuses (420 pg/h) was calculated to be approximately twice the cortisol production rate into an adrenal vein of term fetal lambs reported by Chester-Jones et al (25). Significant elevations in serum cortisol levels occurred in both control and glucosetreated fetuses to levels approximating those seen in the near-term fetal lamb (23).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The control fetuses reported here underwent significant lung maturation in response to cortisol, as reflected by large and statistically significant increases in SAM flux into their tracheal fluid and in their tracheal fluid phospholipid content, which were much greater than those that occur between days 128 and 130 of gestation during normal maturation of fetal lamb lungs (10,11,23 The dose of cortisol infused to both glucose-treated and control fetuses (420 pg/h) was calculated to be approximately twice the cortisol production rate into an adrenal vein of term fetal lambs reported by Chester-Jones et al (25). Significant elevations in serum cortisol levels occurred in both control and glucosetreated fetuses to levels approximating those seen in the near-term fetal lamb (23).…”
Section: Discussionmentioning
confidence: 94%
“…Warburton (10,11) has reported that both primary hyperinsulinemia with concomitant hypoglycemia, and chronic hyperglycemia with secondary hyperinsulinemia reduce SAM flux into tracheal fluid of fetal lambs. Before 128 d gestation, SAM flux into tracheal fluid in the current experiment was similar to Warburton's previously reported data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warburton et al (16) have recently reported that primary hyperinsulinemia reduces surface active material flux in tracheal fluid of fetal lambs in the presence of intrauterine hypoglycemia. Taken together with the results of the current study, these data implicate hyperinsulinemia as an etiologic factor in the reduction of SAM flux.…”
Section: Methodsmentioning
confidence: 99%
“…Warburton et al (16) recently reported that primary hyperinsulinemia reduces surface active material flux in tracheal fluid of fetal lambs. However, the insulintreated lambs in this study became hypoglycemic relative to controls.…”
Section: Introductionmentioning
confidence: 99%